Correlation of ICU Nurses' Cognitive Level with Their Attitude and Behavior toward the Prevention of Ventilator-Associated Pneumonia. (31st March 2022) - Chen, Sujun; Hua, Li; Jin, Qianqian; Wang, Hezhuo
Abstract : Objective . To analyze the correlation of ICU nurses' cognitive level with their attitude and behavior toward the prevention of ventilator-associated pneumonia (VAP). Methods . A total of 90 ICU nurses working in the adult internal medicine ICU, adult surgery ICU, subacute respiratory care ward, etc. from January 2018 to June 2019 were chosen as the subjects to carry out questionnaire survey with the cognition scale, and the correlation analysis on their cognitive level, attitude, and behavior toward the prevention of VAP was conducted. Results . The linear fitting analysis finding showed that the cognitive level presented a positive correlation with the attitude score and behavior score ( R 2  = 0.668, 0.734). Conclusion . Improving ICU nurses' cognitive level, attitude, and behavior toward preventing VAP is conducive to the upgrade of their quality of nursing services. In addition, the ICU nurses' cognitive level is positively correlated with their attitude and behavior.